EFFECT OF 4 wt% HYDROXYAPATITE PASTA ON DENTAL EMAIL HARDNESS - James Hartono Santoso; Anastasia Elsa Prahasti; Elline (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Dental erosion can affect the dental demineralization due to the pH level that is below the critical pH of 5,5 resulting a decrease in dental enamel hardness. Remineralization is needed to bring back the mineral loss. Hydroxyapatite is similar to inorganic components in dental enamel dan have biocompatible properties. Hydroxyapatite with 4 wt% concentration has a Ca/P molar ratio close to 1,67, which is similar to the human enamel and can regenerate enamel. This study is aimed to analyze the effects of 4 wt% hydroxyapatite paste on dental enamel hardness for 7 and 14 days. Material and Methods: 20 maxillary premolars were divided into 4 groups. Group A1 were applied with 4 wt% hydroxyapatite paste for 30 minutes each day for 7 days, group A2 were applied with 4 wt% hydroxyapatite paste for 30 minutes each day for 14 days, group B1 were immersed with artificial saliva for 7 days, and group B2 were immersed with artificial saliva for 14 days. All groups were immersed with artificial saliva and was incubated for 24 hours at 37°C. Hardness measurements were carried out at the start, after erosion, and at the end of the experiment. Dental enamel hardness was measured with Vickers Hardness Tester (Shimadzu HMV G-21 Series). Dental enamel hardness data were analysed with GLM Repeated Measure ANOVA test (p<0,05) and One-way ANOVA test (p<0,05). Results and Discussions: The result showed dental enamel hardness number after 4 wt% hydroxyapatite paste application showed significant difference than untreated group, which was immersed in artificial saliva. Dental enamel hardness number after 4 wt% hydroxyapatite paste application for 14 days showed significant difference than 7 days. Conclusion: It can be concluded that 4 wt% hydroxyapatite paste application for 14 days resulted in an increase of dental enamel hardness as in normal condition of dental enamel before erosion